Brand-driven UX: Designing workshop guidelines to create brand-driven interactions in digital products - RICHARDSON, AGNES (My University, 2022)
With an intense increase in digitalization, many companies’ touch-points and products are online. Nowadays, digital products are among the most frequent contact points between consumers and companies, i.e. brand touch-points. Every interaction with digital products contributes to how the user experiences the brand. Therefore, digital products have become essential to the overall customer and brand experience. Consequently, it is critical to design digital products to trigger specific emotions and associations in the user; beyond satisfying user needs, they should express the brand’s story and values. However, there is a gap in research paying attention to branding and UX design fields in tandem. Consequently, there are few methods to include both perspectives of UX design and branding in practice. Although still quite ambiguous about what determines a good user experience, researchers agree that attention to detail and the big-picture increase the chances for a "better user experience" [75] [31] [76] [65]. Micro-interactions are often overseen as they can be considered intangible and subtly compared with other functional components. However, micro-interactions influence perceived product quality and brand loyalty, making them central in designing digital brand experiences [65]. This project investigates how UX designers can reinforce brand experiences in digital products by considering micro-interactions by answering: How can UX designers be supported in designing brand experience-driven interactivity in digital products? The project aims to enable a new perspective for UX designers on how digital products can be designed to experiences to affect the brand experience and create branddriven micro-interactions. The project followed a hypothesis-driven design and research through a design approach. In the early phases of the project, the problem area was explored by conducting interviews, focus groups and benchmarking. The outcome was analyzed in synthesized into three primary insights and workshop requirements. A workshop series of steps was designed, iterated and tested in an evaluative workshop. Finally, the project resulted in a booklet containing workshop guidelines for UX designers and brand strategists.
Keywords: Brand strategy; UX design; Interactions; Branding; Brand manual; Hedonic attributes; Hypothesis driven design